1980
DOI: 10.2214/ajr.135.1.1
|View full text |Cite
|
Sign up to set email alerts
|

CT of the solitary pulmonary nodule

Abstract: Computed tomography (CT) with thin sections (2-5 mm) was used to assess tissue density in 91 apparently noncalcified pulmonary nodules in 88 patients. The study included 45 primary lung malignancies and 13 metastases proven by subsequent lung biopsy or thoracotomy. There were 33 benign lesions of which 13 were biopsy proven. The other 20 nodules were presumed benign on the basis of serial radiography showing no growth. A representative CT number based on the 32 most dense voxels was calculated for each lesion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(33 citation statements)
references
References 30 publications
0
29
1
2
Order By: Relevance
“…Lobulated contour, signifying uneven growth, is often associated with malignant nodules but can be seen in 25% of benign nodules [14] [15] Although most smoothly marginated nodules are benign but up to 21% of malignant nodules may have this feature [14] A spiculated or irregularly marginated nodule displaying a corona radiata sign indicating neoplastic infiltration and distortion on neighboring tissues is almost certainly a sign of malignancy.…”
Section: Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobulated contour, signifying uneven growth, is often associated with malignant nodules but can be seen in 25% of benign nodules [14] [15] Although most smoothly marginated nodules are benign but up to 21% of malignant nodules may have this feature [14] A spiculated or irregularly marginated nodule displaying a corona radiata sign indicating neoplastic infiltration and distortion on neighboring tissues is almost certainly a sign of malignancy.…”
Section: Marginsmentioning
confidence: 99%
“…Siegelman et al (1980) suggested 164 Hounsfield units as threshold above which the nodules are considered benign. It was presumed that diffuse calcification likely accounts for the higher CT numbers of some benign lesions [14]. Xu DM et al (2009) concluded that baseline nodule density and changes in nodule features cannot be used to discriminate between benign and malignant solid indeterminate pulmonary nodules, but an increase in density is suggestive for malignancy and required a shorter follow-up or a biopsy [31].…”
Section: Ct Densitometrymentioning
confidence: 99%
“…In the differentiation of benign and malignant pulmonary masses, 2 radiographic findings give indications of a benign lesion: the presence of calcifications in the mass, and stability of the mass [5][6][7][8][9]. A benign pattern of the calcifications has been considered necessary to exclude malignancy [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of diffusely disseminated pulmonary nodules, identification of diffusely disseminated pulmonary nodules, identification of calcifications in the nodules has been helpful in limiting the differential diagnosis [14]. Conventional radiography and conventional tomography have been used to detect calcifications, but they have been largely replaced by CT [7][8]. However, CT has several inherent problems, including motion artifacts and a variety of reconstruction algorithms used different scanners.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Siegelman et al [4] first demonstrated a group of benign pulmonary nodules without overt calcification but with CT numbers (attenuation values) above those of neoplasms.…”
mentioning
confidence: 99%